Insights into the pathogenesis and differential diagnosis of clival lesions in an individual from a 16th-century-CE mass grave at Mohács (Southwestern Hungary) - Marcos De Andrés Montero; Luca Kis; Viktor Vig; Réka Kocsmár; Albert Zink; Frank Maixner; Bianca Mari; Alexandra Mussauer; Antal Sklánitz; András Palkó; Ádám Perényi; Árpád Szabó; et al. (PLoS ONE, 2026)
The aim of our paper is to present and discuss in detail the pathological lesions suggestive of tuberculosis observed in a skeleton ( MMG3–75 ) that was excavated from the 16 th -century-CE mass grave No. 3 of the Mohács National Memorial Site (Sátorhely, southwestern Hungary). The differential diagnoses of the observed bony changes, with special attention to the clival alterations, are presented. During the macromorphological, radiological, and digital microscopic examination of MMG3–75 , the skull base showed mild cortical erosion and multiple, well-circumscribed osteolytic lesions at the clivus clearly evidenced by 3D imaging. In addition, endocranial granular impressions and abnormal blood vessel impressions were observed in multiple locations on the inner skull surface. Based on the differential diagnosis of the clival changes and their co-occurrence with endocranial alterations indicative of tuberculous meningitis (granular impressions and abnormal blood vessel impressions), they were most likely due to tuberculous involvement of the skull base. Additional aDNA analysis provided no evidence for the presence of Mycobacterium tuberculosis DNA in MMG3–75 . To the best of our knowledge, MMG3–75 is the first reported archaeological case of tuberculous clival osteomyelitis with associated meningitis, giving us a unique insight into the occurrence of an extremely rare manifestation of tuberculosis in mediaeval Hungary.